Analisis Komparatif Strategi Mitigasi Emisi Gas Rumah Kaca dan Kinerja Pelaporan Berbasis GRI 305 pada Industri Hulu Migas: Studi Kasus Pertamina Hulu Energi (Indonesia) dan PTT Exploration and Production (Thailand) - Muhammad Yasin Atsaqib; Indah Fachriah; Maria Ariesta Utha (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Climate change compels the upstream oil and gas industry to undergo an energy transition and enhance the transparency of emissions reporting. This study aims to conduct a comparative analysis of Greenhouse Gas (GHG) emission mitigation strategies and sustainability reporting performance—based on Global Reporting Initiative (GRI) 305 standards—between Pertamina Hulu Energi (PHE) of Indonesia and PTT Exploration and Production (PTTEP) of Thailand. A descriptive qualitative method employing a comparative case study approach is utilized. Data were gathered through a documentary review of sustainability reports, annual reports, and the Nationally Determined Contribution (NDC) documents of both nations. The study's findings are expected to identify gaps regarding the effectiveness of decarbonization strategies and the quality of emissions disclosures, as well as to formulate best practices to support national Net Zero Emission (NZE) targets.